PINK1 Protects Against Gentamicin-Induced Sensory Hair Cell Damage: Possible Relation to Induction of Autophagy and Inhibition of p53 Signal Pathway - Yang, Qianqian; Zhou, Yiwei; Yin, Haiyan; Li, Hongrui; Zhou, Meijuan; Sun, Gaoying; Cao, Zhixin; Man, Rongjun; Wang, Haibo; Li, Jianfeng (Frontiers in Molecular Neuroscience, 2018)
Phosphatase and tensin homolog homologue (PTEN)-induced putative kinase 1 (PINK1) is a gatekeeper of mitochondrial quality control. The present study was aimed to examine whether PINK1 possesses a protective function against gentamicin (GM)-induced sensory hair cell damage in vitro. The formation of parkin particles (a marker revealing the activation of PINK1 pathway which is a substrate of PINK1 and could signal depolarized mitochondria for clearance) and autophagy were determined by immunofluorescence staining. The expressions of PINK1, LC3B, cleaved-caspase 3 and p53 were measured by Western blotting. The levels of reactive oxygen species (ROS) and apoptosis were respectively evaluated by DCFH-DA staining, Annexin V Apoptosis Detection Kit and TUNEL staining. Cell viability was tested by a CCK8 kit. We found that treatment of 400 μM GM elicited the formation of ROS, which, in turn, led to PINK1 degradation, parkin recruitment, autophagy formation, an increase of p53 and cleaved-caspase 3 in HEI-OC1 cells and murine hair cells (HCs). In contrast, co-treatment with ROS scavenger N-acetyl-L-cysteine (NAC) inhibited parkin recruitment, alleviated autophagy and p53 pathway-related damaged-cell elimination. Moreover, PINK1 interference contributed to a decrease of autophagy but an increase of p53 level in HEI-OC1 cells in response to GM stimulus. Findings from this work indicate that PINK1 alleviates the GM-elicited ototoxicity via induction of autophagy and resistance the increase of p53 in hair cells.